Plant Connections Leader's Guide - Janice Easton; Deborah J. Glauer (EDIS)
4-H PLANT CONNECTIONS was developed through a team effort of the Department of Family, Youth and Community Sciences, Institute of Food and Agricultural Sciences, The Florida 4-H Youth Development Office and the Departments of Horticultural Sciences and Environmental Horticulture, University of Florida. Original publication date May 1997. Reviewed June 2002.